Modeling, simulation and analysis of electromechanical impedance-based SHM using finite element - Antunes, Rothschild Alencastro; Cortez, Nicolás E.; Gianesini, Bárbara; Turra, Antônio E. [UNESP]; Filho, Jozué Vieira [UNESP] (My University, 2017)
Electromechanical impedance-based (EMI) damage detection techniques are based on the capability of piezoelectric materials to act as sensors and actuators and they have contributed to the development of structural health monitoring (SHM) systems. Classic techniques use a PZT (Pb-lead Zirconate Titanite) transducer attached to the monitored structure and measure the impedance signature of the couple PZT-Structure. However, EMI based techniques are depending of different factors such as frequency range, number of PZT, ambient temperature, type of structure, among others. Thus, in order to demonstrate the effectiveness of EMI-based methods, it is necessary to carry out practical experiments, which is not a trivial task when such factors have to be considered. Therefore, in this paper, it is presented an EMI-based finite element (FE) model developed using PZFlex® software, which is based on FE. Two different structures were simulated and evaluated: a rectangular aluminum plate and a steel pipe. Simulated results were compared with practical ones and show that the proposed model can be a powerful tool for developing EMI-based SHM techniques.